Properties of a Ribonucleoprotein Particle Isolated from Nonidet P-40-Treated Rous Sarcoma Virus - Davis, Nancy L. (1972)
A ribonucleoprotein particle containing about 20% ribonucleic acid (RNA), and containing little if any phospholipid or glucosamine, was recovered in high yield after treatment of Schmidt-Ruppin strain of Rous sarcoma virus and B77 virus with the nonionic detergent Nonidet P-40. This structure, which probably derives from the internal ribonucleoprotein filament described in electron microscopy studies, contained 80 to 90% of the viral 60 to 70S RNA and only about 10% of the protein present in intact virions. It sedimented in glycerol density gradients at approximately 130S and had a buoyant density in sucrose of about 1.34 g/ml. Studies with (32)P-labeled virus indicated that the ribonucleoprotein particle contained approximately 30 4S RNA molecules per 10(7) daltons of high-molecular-weight viral RNA. Intact virions contained about 70 4S RNA molecules per 10(7) daltons of high-molecular-weight RNA. Electrophoretic studies in dodecyl sulfate-containing polyacrylamide gels showed that the ribonucleoprotein particle contained only 5 of the 11 polypeptides found in the virion; of these the major component was a polypeptide weighing 14,000 daltons.